Introspecting entrepreneurship from a tawhidic perspective - Anor Salim, Farah Akmar; Salima, Anor; Mhd Sarif, Suhaimi; Maidin, Ainul Jaria; Ismail, Yusof; Zainudin, Dolhadi (Accounting Research Institute (ARI) UiTM Shah Alam, 2018)
The concept of ethical attitude and standard in business dealings has long been argued in the academic world. The current implication on skills and ethical concepts and ideas of Malaysian entrepreneurs from Islamic practices is brie y outlined in the study. Capitalizing on a comprehensive set of questionnaires containing information on respondent’s pro le, characteristics and educational background, one hundred twenty-one (121) entrepreneurs were surveyed using convenience sampling. The practice of Islamic skills and ethics among Malaysian entrepreneurs in numerous business sectors are discussed in the study. The study postulates that the awareness gained from well-being (falāh) in life and excellence (itqān) in work in business organisations can be derived from the pursuit of the Tawhidic principle. A set of close ended questions that contains individual’s characteristics and principles were distributed to entrepreneurs from various business sectors and work experiences for the purpose. The study managed to collect 121 completed questionnaires from Malaysian entrepreneurs. The study contributes signi cant information to the academic world as well as to corporations and governments in conducting business. Finally, the study concludes with the discussion on the proposed business practices and recommends future implementation in achieving entrepreneurial success.